A Double Triage and Telemedicine Protocol to Optimize Infection Control in an Emergency Department in Taiwan During the COVID-19 Pandemic: Retrospective Feasibility Study - Lin, Chien-Hao; Tseng, Wen-Pin; Wu, Jhong-Lin; Tay, Joyce; Cheng, Ming-Tai; Ong, Hooi-Nee; Lin, Hao-Yang; Chen, Yi-Ying; Wu, Chih-Hsien; Chen, Jiun-Wei; Chen, Shey-Ying; Chan, Chang-Chuan; et al. (JMIR Publications, 2020)
BackgroundFrontline health care workers, including physicians, are at high risk of contracting coronavirus disease (COVID-19) owing to their exposure to patients suspected of having COVID-19. ObjectiveThe aim of this study was to evaluate the benefits and feasibility of a double triage and telemedicine protocol in improving infection control in the emergency department (ED). MethodsIn this retrospective study, we recruited patients aged ≥20 years referred to the ED of the National Taiwan University Hospital between March 1 and April 30, 2020. A double triage and telemedicine protocol was developed to triage suggested COVID-19 cases and minimize health workers' exposure to this disease. We categorized patients attending video interviews into a telemedicine group and patients experiencing face-to-face interviews into a conventional group. A questionnaire was used to assess how patients perceived the quality of the interviews and their communication with physicians as well as perceptions of stress, discrimination, and privacy. Each question was evaluated using a 5-point Likert scale. Physicians' total exposure time and total evaluation time were treated as primary outcomes, and the mean scores of the questions were treated as secondary outcomes. ResultsThe final sample included 198 patients, including 93 cases (47.0%) in the telemedicine group and 105 cases (53.0%) in the conventional group. The total exposure time in the telemedicine group was significantly shorter than that in the conventional group (4.7 minutes vs 8.9 minutes, P<.001), whereas the total evaluation time in the telemedicine group was significantly longer than that in the conventional group (12.2 minutes vs 8.9 minutes, P<.001). After controlling for potential confounders, the total exposure time in the telemedicine group was 4.6 minutes shorter than that in the conventional group (95% CI −5.7 to −3.5, P<.001), whereas the total evaluation time in the telemedicine group was 2.8 minutes longer than that in the conventional group (95% CI −1.6 to −4.0, P<.001). The mean scores of the patient questionnaire were high in both groups (4.5/5 to 4.7/5 points). ConclusionsThe implementation of the double triage and telemedicine protocol in the ED during the COVID-19 pandemic has high potential to improve infection control.